Adaptive Sampling for Interactive Simulation of Granular Material - Gupta, Samraat; Keyser, John (Computer animation and virtual worlds, 2025)
ABSTRACT We present a method for simulating granular materials faster within a position based dynamics framework. We do this by combining an adaptive particle sampling scheme with an upsampling approach. This allows for faster simulations in interactive applications, while maintaining visual resolution. Particles are merged or split based on their distance from the boundary, allowing for high details in areas of importance such as the surface and edges. Merging particles into a single particle reduces the number of particles for which collisions have to be simulated, thus reducing the overall simulation time. The adaptive sampling technique is then combined with an upsampling scheme that gives the coarser particle simulation the appearance of much finer resolution. We present a method for simulating granular materials faster within a position based dynamics framework. We do this by combining an adaptive particle sampling scheme with an upsampling approach.